Factors affecting consumers preferences on fast food items in Bangladesh - Ullah, G. M. Shafayet; Islam, Nazrul (Journal of Applied Business Research (JABR), 2016)
This article was published in Journal of Applied Business Research (JABR) [© 2010 Journal of Applied Business Research (JABR)] and the definite version is available at : http://cluteinstitute.com/ojs/index.php/JABR/article/view/313/303 The article website is at: http://www.cluteinstitute.com/journals/journal-of-applied-business-research-jabr/ DOI: http://dx.doi.org/10.19030/jabr.v26i4.313